1982
DOI: 10.1159/000269427
|View full text |Cite
|
Sign up to set email alerts
|

Veränderungen der vaginalen Flora von Trichomoniasispatientinnen durch die Vakzination mit Solco Trichovac

Abstract: Das Vaginalsekret wurde bei 36 Patientinnen mit Trichomonadenkolpitis vor, während und nach der Impfung mit SolcoTrichovac hinsichtlich Veränderungen der Bakterienflora untersucht. Alle Patientinnen sprachen auf die Impfung an und wurden trichomonadenfrei. Die initial bei alien Patientinnen pathologische Vaginalflora erfuhr in einigen Fallen bemerkenswerte Veränderungen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has previously been demonstrated that the treatment of trichomoni asis with Gynatren/SolcoTrichovac results in the re-establishment of nor mal bacterial flora in the vagina [1,5,6], This fact plus the favourable reports of others in treating non-specific vaginitis with this immunotherapeutic [7; pers. commun.]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that the treatment of trichomoni asis with Gynatren/SolcoTrichovac results in the re-establishment of nor mal bacterial flora in the vagina [1,5,6], This fact plus the favourable reports of others in treating non-specific vaginitis with this immunotherapeutic [7; pers. commun.]…”
Section: Discussionmentioning
confidence: 99%
“…Since both non-specific colpitis and trichomoniasis are characterized by anaerobic mixed flora [1] with a decrease in normal lactobacilli, a rise in vaginal pH and the appearance of aberrant lactobacilli [6], it seemed appropriate to study the effect of Gynatren/SolcoTrichovac in non-specific colpitis. Treat ment with this preparation represents an immunotherapeutic attack against those aberrant, coccoidal lactobacilli [2], Study Design A series of 130 patients with non-specific colpitis were entered into the study and treated with three intramuscular injections of 0.5 ml Gynatren at intervals of 14 days.…”
Section: Introductionmentioning
confidence: 99%